Pain during and after coronavirus disease 2019: Chinese perspectives - Jiang, Feng (Pain Rep, 2021)
The coronavirus disease 2019 (COVID-19) global pandemic poses a major threat to human health and health care systems. Urgent prevention and control measures have obstructed patients' access to pain treatment, and many patients with pain have been unable to receive adequate and timely medical services. Many patients with COVID-19 report painful symptoms including headache, muscle pain, and chest pain during the initial phase of the disease. Persistent pain sequela in patients with COVID-19 has a physical or mental impact and may also affect the immune, endocrine, and other systems. However, the management and treatment of neurological symptoms such as pain are often neglected for patients hospitalized with COVID-19. Based on the China's early experience in the management of COVID-19 symptoms, the possible negative effects of pre-existing chronic pain in patients with COVID-19 and the challenges of COVID-19 prevention and control bring to the diagnosis and treatment of chronic pain are discussed. This review calls to attention the need to optimize pain management during and after COVID-19.